'We are the vocal minority': The Safe Standing movement and breaking down the state in English football. (November 2021) - Turner, Mark
Lord Justice Taylor's final report into the Hillsborough stadium disaster recommended that all Premier League and Championship football grounds in England and Wales should become all-seated and that football supporters would eventually become 'accustomed and educated to sitting'. Thirty years later, thousands of fans continue to stand at matches but in areas not designed for them to do so. This ritual has become a source of conflict between clubs, supporters and official safety bodies. In 2018, the UK Sports Minister claimed that despite this problem, there remained no desire amongst top clubs to change the all-seating policy and that it was only a 'vocal minority' who wanted to see the permanent return of standing in English football. However, supporters, networked through the national Football Supporters Association, had been actively mobilizing a social movement against the legislation for over 20 years. In this article, I use relational sociology to analyse empirical snapshots of the latest phase of this movement, 'Safe Standing', to show how the switching and cooperation of supporter networks and their tactics were successful in breaking down the state to create new political opportunities. In doing so, the article reveals the key characteristics of safe standing, including conflict, organizational form and intersubjective motivations, to represent the collective – but also often complex and contradictory – responses to the neoliberal political economy which English football, and society more broadly, has inhabited over the past 30 years.